Memory Design Techniques for Low Energy Embedded Systems - Macii, Alberto; Benini, Luca; Poncino, Massimo (Springer US, 2002)
Memory Design Techniques for Low Energy Embedded Systems centers one of the most outstanding problems in chip design for embedded application. It guides the reader through different memory organizations and technologies and it reviews the most successful strategies for optimizing them in the power and performance plane
Keywords: Engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design; Computer Systems Organization and Communication Networks; Electrical Engineering; Computer organization; Computer-aided engineering; Electrical engineering; Electronic circuits; Speicherverwaltung; Eingebettetes System